the Integrated Desalination Innovation for Clean Water Independence and Food Security in Coastal Villages: Collaboration Farmers, Village-Owned Enterprises, and Places of Worship: Integrated Desalination Innovation for Clean Water Independence and Food Security in Coastal Villages: Collaboration Farmers, Village-Owned Enterprises, and Places of Worship - Opi Irawansah; Susanti Susanti; Anwar Ma’ruf; Fajar Nurwibowo; Isna Hikmawati; Rum Sapundani; Nuh Almahdi; Rasyid Miftah; Dayna Rizkya; Myra Zaqia Alwi; Nandita Vitarin Putri Maulida (Adi Widya : Jurnal Pengabdian Masyarakat, 2026)
Ujung Alang Village, located in Kampung Laut Subdistrict, Cilacap Regency, is a coastal area facing critical challenges in freshwater availability due to seawater intrusion and limited access to clean water sources. This condition affects domestic needs, sanitation, and the productivity of local agriculture. The Kosabangsa 2025 Program was implemented as a strategic effort to enhance water self-sufficiency and food security through the application of solar-powered Reverse Osmosis (RO) desalination technology. This community service initiative involved Banyu Urip Sentosa Village-Owned Enterprise (BUMDes) as the manager of the clean water business unit and the Mekar Sari Farmer Group as beneficiaries of desalinated water for agricultural irrigation. The methods included identifying community water needs, providing technical training on RO operation, installing the desalination system, mentoring BUMDes in business management, applying desalinated water for agricultural irrigation, and conducting monitoring and evaluation of water quality and its impacts on farmland. The results show that the desalination system successfully supplied safe drinking water for households and religious facilities, while also providing non-potable water for coastal farming activities. Community capacity increased through training and mentoring, and BUMDes gained opportunities to develop a sustainable village-based clean water enterprise. Overall, this program demonstrates that integrating appropriate technology, renewable energy, and community empowerment can significantly improve clean water independence, strengthen food security, and generate positive economic impacts for coastal communities. This collaborative model has strong potential to be replicated in other coastal areas with similar challenges and characteristics. Keywords: desalination, reverse osmosis, solar energy, BUMDes, community empowerment, coastal village, Kosabangsa 2025